2020
DOI: 10.21522/tijar.2014.07.01.art004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Factors Influencing Pre-Service Teachers’ Mathematical Knowledge for Teaching (MKT) Mathematics in Ghanaian Basic Schools

Abstract: Introduction: Knowledge about teaching mathematics remains a contentious issue in the preparation of pre-service teachers. This study assessed factors influencing pre-service teachers' mathematical knowledge for teaching (MKT) mathematics in Ghanaian basic schools.Methods: The cross-sectional survey design was adopted for this study. A total of 998 pre-service teachers from ten (10) public colleges of education were sampled via multi-stage sampling technique for the study. Structured questionnaire and unstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This shows that the skill of using knowledge in solving non-routine problems requires the involvement of the ability to connect various concepts, experience involved in problem solving activities and complete prerequisite knowledge which is also influenced by the amount of time available for learning, the characteristics of the instructor and the content being studied [37]. Besides that, Narh-Kert and Ampadu [38] revealed that the factors that influence the ability of preservice teachers of mathematics are the way of conveying knowledge of mathematics, perceptions of mathematics as a subject, perceptions of teaching and learning mathematics and attitudes towards mathematics. Of these various factors, attitudes to mathematics tend to underlie the mathematical performance of preservice mathematics teachers [39].…”
Section: The Statistical Relationship Between Students Background And...mentioning
confidence: 98%
See 1 more Smart Citation
“…This shows that the skill of using knowledge in solving non-routine problems requires the involvement of the ability to connect various concepts, experience involved in problem solving activities and complete prerequisite knowledge which is also influenced by the amount of time available for learning, the characteristics of the instructor and the content being studied [37]. Besides that, Narh-Kert and Ampadu [38] revealed that the factors that influence the ability of preservice teachers of mathematics are the way of conveying knowledge of mathematics, perceptions of mathematics as a subject, perceptions of teaching and learning mathematics and attitudes towards mathematics. Of these various factors, attitudes to mathematics tend to underlie the mathematical performance of preservice mathematics teachers [39].…”
Section: The Statistical Relationship Between Students Background And...mentioning
confidence: 98%
“…Academic ability is a combination of learning experience and skills to use knowledge consistently in life that provides long-term retention of information. The ability of a preservice teacher is influenced by perceptions about mathematics, the curriculum, the learning process, the relevance of theory and practice, gender, and attitudes towards mathematics [38], [41]. These factors, in addition to affecting general math skills, also affect the HOTS of preservice teachers because mathematics is actually about thinking processes and not just calculating skills.…”
Section: The Statistical Relationship Between Students Background And...mentioning
confidence: 99%